Telomere length and pancreatic cancer: a case-control study - Skinner, Halcyon G. (2012)
BACKGROUND: Telomeres, the ends of chromosomes, are critical for maintaining genomic stability and grow shorter with age. Shortened telomeres in pancreatic tissue play a key role in the pathogenesis of pancreatic cancer, and shorter telomeres in peripheral blood leukocytes (PBLs) have been associated with increased risk for several cancer types. We hypothesized that shorter blood telomeres are associated with higher risk for pancreatic cancer. METHODS: Telomere length was measured in PBLs using quantitative real-time PCR in 499 cases with pancreatic cancer and 963 cancer-free controls from the Mayo Clinic. Odds ratios and confidence intervals were computed using logistic generalized additive models adjusting for multiple variables. Results: In multivariable adjusted models we observed a significant non-linear association between telomere length in peripheral blood samples and the risk for pancreatic cancer. Risk was lower among those with longer telomeres compared to shorter telomeres across a range from the 1%ile to 90%ile of telomere length. There was also some evidence for higher risk among those with telomeres in the longest extreme. CONCLUSIONS: Short telomeres in peripheral blood are associated with an increased risk for pancreatic cancer across most of the distribution of length, but extremely long telomeres may also be associated with higher risk. IMPACT: Although the temporality of this relationship is unknown, telomere length may be useful as either a marker of pancreatic cancer risk or of the presence of undetected pancreatic cancer. If telomere shortening precedes cancer incidence, interventions to preserve telomere length may be an effective strategy to prevent pancreatic cancer.